(untitled) (Jurnal Destinasi Pariwisata, 2025)
The tourist attraction of Mount Boga is a destination in Paser Regency known for its stunning panoramic views, offering visitors the sensation of being above the clouds. This study aims to analyze the influence of attractiveness and tourist motivation on visits to the natural tourism site of Mount Boga. The research employs a descriptive quantitative approach. The sampling technique used is accidental sampling, with a sample size of 100 tourists who have visited or are currently visiting Mount Boga. Data were collected through questionnaires, observations, interviews, and documentation. The data analysis technique applied in this study uses a Likert scale and is tested using simple linear regression analysis. The findings indicate that attractiveness and tourist motivation significantly influence visits. Statistical tests conducted as part of the research on the influence of natural tourism attractiveness and tourist motivation at Mount Boga in Paser Regency reveal several key results. Validity tests for all variables show that the calculated R-value is greater than the table R-value (0.446), indicating validity. The reliability test for variable X results in a Cronbach Alpha value of 0.656 > 0.6. Through simple linear regression analysis, a regression coefficient of 0.588 was found, indicating a positive relationship. Hypothesis testing (t-test) demonstrates a significance value of 0.001 < 0.05 and a calculated t-value of 7.198 > t-table value of 1.198. Thus, it can be concluded that the relationship between the attractiveness of the tourist site and tourist motivation at Mount Boga can lead to an increase in visitors. Proper management of the tourist attraction can stimulate growth in tourist numbers, creating positive impacts on the local community and environment.